Removal and Recovery of Silver by Dynamic Adsorption on Bentonite Clay Using a Fixed-Bed Column System - M. L. Cantuaria; E. S. Nascimento; A. F. Almeida Neto; O. A. A. dos Santos; M. G. A. Vieira (Adsorption Science & Technology)
Several studies have focused on the removal and recovery of precious metal ions from industrial wastewater due to their environmental and economic importance. Adsorption on bentonite clays has been shown to possess a high removal potential for several metal ions. We herein investigated the dynamic adsorption of silver using a fixed-bed column and a calcined bentonite clay called Verde-lodo as an adsorbent. A fluid dynamic study was performed to evaluate the adsorption system's metal-ion removal capacity (q u and q t ), the mass transfer zone and the percentage of total removal according to different effluent's flow. Adsorption–desorption cycles were carried out using nitric acid as an eluent to evaluate the useful lifetime of the column. The breakthrough curves were fitted to the Bohart–Adams model (quasichemical). Moreover, the zeta potential was analyzed to explain the difference between the removal capacity obtained for the static and dynamic systems.